Intestinal antibody responses to a live oral poliovirus vaccine challenge among adults previously immunized with inactivated polio vaccine in Sweden. Issue 4 (28th August 2019) - Brickley, Elizabeth B; Connor, Ruth I; Wieland-Alter, Wendy F; Collett, Marc S; Hartford, Marianne; Van Der Avoort, Harrie; Boesch, Austin W; Weiner, Joshua A; Ackerman, Margaret E; McKinlay, Mark A; Arita, Minetaro; Bandyopadhyay, Ananda S; et al.
Abstract : Background: Our understanding of the acquisition of intestinal mucosal immunity and the control of poliovirus replication and transmission in later life is still emerging. Methods: As part of a 2011 randomised, blinded, placebo-controlled clinical trial of the experimental antiviral agent pocapavir (EudraCT 2011-004804-38), Swedish adults, aged 18–50 years, who had previously received four doses of inactivated polio vaccine (IPV) in childhood were challenged with a single dose of monovalent oral polio vaccine type 1 (mOPV1). Using faecal samples collected before and serially, over the course of 45 days, after mOPV1 challenge from a subset of placebo-arm participants who did not receive pocapavir (N=12), we investigated the kinetics of the intestinal antibody response to challenge virus by measuring poliovirus type 1-specific neutralising activity and IgA concentrations. Results: In faecal samples collected prior to mOPV1 challenge, we found no evidence of pre-existing intestinal neutralising antibodies to any of the three poliovirus serotypes. Despite persistent high-titered vaccine virus shedding and rising serum neutralisation responses after mOPV1 challenge, intestinal poliovirus type 1-specific neutralisation remained low with a titer of ≤18.4 across all time points and individuals. Poliovirus types 1-specific, 2-specific and 3-specific IgA remained below the limit of detection for all specimens collected postchallenge. Interpretation: In contrast to recent studies demonstrating brisk intestinal antibody responses to oral polio vaccine challenge in young children previously vaccinated with IPV, this investigation finds that adults previously vaccinated with IPV have only modest intestinal poliovirus type 1-specific neutralisation and no IgA responses that are measurable in stool samples following documented mOPV1 infection.